Asymmetric intramolecular C–H insertion of N-tosyl diazoimine intermediate from triazole derivative by axially chiral dirhodium(II) carboxylate complex - Lu, Wenjie; Murai, Takuya; Kyan, Ryuji; Kobayashi, Yusuke; Kawabata, Takeo; Furuta, Takumi (Synlett, 2025)
The asymmetric intramolecular C–H insertion of an in situ generated diazoimine intermediate derived from N-tosyl-1,2,3-triazoles was investigated. Among the chiral paddlewheel dirhodium(II) complexes screened, only C2-symmetric-like dirhodium(II) carboxylate complexes bearing axially chiral amino acid derivatives as ligands proved to be effective in asymmetric induction. This catalyst afforded 2,3-disubstituted tetrahydrofurans with reasonable enantioselectivity for the cis-isomer.
Keywords: C–H insertion; Asymmetric reaction; Paddlewheel dirhodium(II) complex; Triazole; Diazoimine